Spies and their masters intelligence-policy relations in democratic countries - Faini, Matteo (Routledge, 2021)
"This book delves into the secret histories of the CIA, the FBI and British and Italian intelligence to study how policymakers can control intelligence agencies and when these agencies will try to remove their own government. For every government they serve, intelligence agencies are both a threat and a necessity. They often provide vital information for national security, but the secrets they possess can also be used against their own masters. This book introduces subversion paradox theory to provide a social scientific explanation of the unequal power dynamic resulting from an often-fraught relationship between agencies and their 'masters'. The author also makes a case for the existence of 'deep state' conspiracies, including in highly developed democracies, and cautions those who denounce their existence that trying to control intelligence by politicizing it is likely to backfire. An important intervention in the field of intelligence studies, this book will be indispensable for intelligence professionals and policymakers in understanding and bridging the cultural divide between these two groups. It will also make for a fascinating and informative read to scholars and researchers of diplomacy, foreign policy, international relations, strategic and defence studies, security studies, political studies, policy making, and comparative politics"